2019
DOI: 10.5964/jspp.v7i1.897
|View full text |Cite
|
Sign up to set email alerts
|

Threats to human rights: A general review

Abstract: It has been seventy years since signing the Declaration of Human Rights, yet human right violations are still happening across the globe. This review asks the question – what is the impact of perceived threat on changing support for human rights into support for not-all-humans’ rights? In approaching human rights violations with a four-level model – institutions, cultures, groups, and individuals –, issues of capabilities, historical emotions, connectedness, and personality emerge. At the heart of these is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 171 publications
(146 reference statements)
0
22
0
1
Order By: Relevance
“…In line with previous studies, which have shown that those who appreciate freedom are particularly guided by that value in assessing moral issues [55], high endorsement of liberty predicted less positive attitudes towards the implementation of surveillance technologies. In turn, RWA was a positive predictor of acceptance of these technologies as in previous studies on the possible trade-off between civil rights and security under terrorist threats [51]. Moreover, as previous research has shown that RWA is particularly related to the need for safety and risk minimisation [43,44], we examined whether RWA moderated the relationship between both perceived threat and lack of control and acceptance of surveillance technologies.…”
Section: Plos Onementioning
confidence: 62%
See 2 more Smart Citations
“…In line with previous studies, which have shown that those who appreciate freedom are particularly guided by that value in assessing moral issues [55], high endorsement of liberty predicted less positive attitudes towards the implementation of surveillance technologies. In turn, RWA was a positive predictor of acceptance of these technologies as in previous studies on the possible trade-off between civil rights and security under terrorist threats [51]. Moreover, as previous research has shown that RWA is particularly related to the need for safety and risk minimisation [43,44], we examined whether RWA moderated the relationship between both perceived threat and lack of control and acceptance of surveillance technologies.…”
Section: Plos Onementioning
confidence: 62%
“…We should stress some limitations of this research. First, both our studies were correlational, so they do not establish causal relationships between the variables; however, it seems more plausible that lack of control, personal threat, RWA and endorsement of liberty predicted support for radical measures counteracting the pandemic than the reverse (see e.g., Carriere, 2019). Second, we did not measure the perceived efficacy of these surveillance technologies, and it would be worth examining directly whether the introduction of such solutions would, in fact, restore the sense of personal control and reduce the sense of threat.…”
Section: Limitations and Future Directionsmentioning
confidence: 83%
See 1 more Smart Citation
“…Political economy and law research explaining how people react and accept human rights 'violations' (e.g. surveillance measures, freedom of speech, lockdowns) under conditions of 'state of exception' like terrorism or the COVID-19 (Carriere, 2019;Bozzoli & Müller, 2011;Scheppele, 2003) can provide a new lenses for studying adoption of the COVID-19 controversial technologies and restrictions Research on political ideologies could further enlighten why people's ideologies and political values may further perplex their reactions and behaviours to such interventions in their human rights.…”
Section: Tourism Demandmentioning
confidence: 99%
“…Individuals express support for human rights, but then drop their support in the next instant (Drolet, Hafer, & Heuer, 2016), subjugate subgroups to only marginal access to liberty (Abrams, Houston, Vyver, & Vasiljevic, 2015), and staunchly support their in-group while condemning an out-group for the same activity (Tarrant, Branscombe, Warner, & Weston, 2012). The threat of the "other" pervades the discussion of who deserves rights (Beck & Plant, 2018;Carriere, 2019;Huddy & Feldman, 2011;Huddy, Feldman, & Weber, 2007;Welch, 2016). This experience of threat and restriction of liberties has a wide range of negative implications for free societies (Carriere, Garney, & Moghaddam, 2018;Jaspal, Carriere, & Moghaddam, 2016;Lauderdale, 2006), including reduced support for freedom of religion (AP-NORC Center for Public Affairs Research, 2015), increased support for surveillance (Cohrs, Kielmann, Maes, & Moschner, 2005), and increased reports of hate crimes and discrimination (Disha, Cavendish, & King, 2011).…”
mentioning
confidence: 99%